Pengembangan Media Pembelajaran Interaktif Berbasis Wordwall pada Mata Pelajaran Al-Qur'an Hadist Untuk Meningkatkan Minat Belajar Siswa di Man Seluma Kab. Seluma Provinsi Bengkulu - Desi Wulandari; Andang Sunarto; Husnul Bahri (UIN Fatmawati Sukarno Bengkulu, 2024)
The objectives of the study are: (1) To determine the effectiveness of the validity of Interactive Learning Media Based on Wordwalls in the Al-Qur'an Hadith Subject. (2) To determine the practicality of the Development of Interactive Learning Media Based on Wordwalls in the Al-Qur'an Hadith Subject to Increase Student Learning Interest at MAN Seluma, Bengkulu Province. (3) To determine the effectiveness of Interactive Learning Media Based on Wordwalls in the Al-Qur'an Hadith Subject to Increase Student Learning Interest at MAN Seluma, Bengkulu Province. The type of research used in this study is quantitative research, the research instrument used is a questionnaire, the data analysis technique used is descriptive statistics, basic assumption tests, classical assumption tests, and hypothesis tests using simple linear regression and multiple linear regression, t-test and F-test. Research results (1) The development in the study is interactive learning media based on wordwalls in learning the Al-Qur'an Hadith of class X students of MAN 1 Seluma. The process of interactive learning media based on wordwall uses the type of research and development (R&D) with a model developed by Thiagaranja, namely the 4-D model and modified into 3-D, namely define, design, and develop. The development of learning media based on animated videos after being validated by 3 expert validators, namely media experts, material experts and subject teachers with the results